An Analysis of Water Contamination& Related Issues (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water is essential for existence. It is  unnecessary to emphasise how vital it is. Water pollution,  on or h&, is among most severe ecological issues  confronting us today. Contaminated substances move in bodies of water like ponds, streams, & oceans & are  dissolved, float in water, or deposit on bed, causing water  pollution. As a result, water quality worsens. This would  be devastating not just for aquatic ecosystems, but toxins  would also seep through & reach groundwater, possibly  polluting water human use in everyday events, together  with drinking. Water contamination can occur in variety of  methods, severe being municipal dirt & industrialised leftover exoneration. Unintended causes of water  contamination comprise contaminants entering water  supply through soils or groundwater system, as well as  rain.. Human farming activities, as well as illegally  disposed of industrial pollutants, are found in soils & groundwater. Organic, inorganic, radioactive, & or types  of pollutants exist.
Keywords: Chemicals; contamination; Pollutants; wastewater; Water pollution